School readiness is more than the child: a latent class analysis of child, family, school and community aspects of school readiness. Issue 1 (12th October 2020) - Christensen, Daniel; Taylor, Catherine L.; Hancock, Kirsten J.; Zubrick, Stephen R.
Abstract: In this paper, we aim to contribute to the understanding of the multidimensional nature of school readiness. In a sample of over 4, 000 Australian children in their first year of school, we used latent class analysis to examine patterns of school readiness based on child, family, school and community characteristics, and examine the relationship between these patterns of school readiness and subsequent outcomes (reading comprehension, school absence and emotional and behavioural difficulties). We identified four distinct groups: a Developmentally Enabled group (70 per cent of children), a Parenting Risk group (16 per cent of children), an Emotionally Immature Risk group (7 per cent of children) and a Language and Developmental Risks group (7 per cent of children). The four profiles showed differential patterns of association with low reading comprehension and emotional and behavioural difficulties at age 8, but no association with school absence. The study highlights the importance of family, school and community factors when considering school readiness.